2014
DOI: 10.1021/pr500220g
|View full text |Cite
|
Sign up to set email alerts
|

Additional Precursor Purification in Isobaric Mass Tagging Experiments by Traveling Wave Ion Mobility Separation (TWIMS)

Abstract: Despite the increasing popularity of data-independent acquisition workflows, data-dependent acquisition (DDA) is still the prevalent method of LC-MS-based proteomics. DDA is the basis of isobaric mass tagging technique, a powerful MS2 quantification strategy that allows coanalysis of up to 10 proteomics samples. A well-documented limitation of DDA, however, is precursor coselection, whereby a target peptide is coisolated with other ions for fragmentation. Here, we investigated if additional peptide purificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…A recent report has shown that TWIMS can improve the quantitative performance of isobaric mass tagging experiments (31,32). Notably, the ion mobility separation of peptide precursor ions reduced the well described issue of co-isolation of peptides and the concomitant decrease in accuracy and precision of TMT quantification (33).…”
Section: Resultsmentioning
confidence: 99%
“…A recent report has shown that TWIMS can improve the quantitative performance of isobaric mass tagging experiments (31,32). Notably, the ion mobility separation of peptide precursor ions reduced the well described issue of co-isolation of peptides and the concomitant decrease in accuracy and precision of TMT quantification (33).…”
Section: Resultsmentioning
confidence: 99%
“…However, in such experiments, the advantages of isobaric tags cannot be exploited, because the total analysis time is increased, and the throughput is reduced. Ion mobility spectrometry (IMS) is compatible with LC and MS and enables increased sensitivity and selectivity in MS and an overall increase in peak capacity without increasing the total analysis time. , So far, LC/IMS/MS experiments using traveling wave ion mobility spectroscopy (TWIMS) and electric field asymmetric ion mobility spectroscopy (FAIMS) have demonstrated that it is possible to uncompress the ratio of isobaric tags in quantitative proteome analysis.…”
mentioning
confidence: 99%
“…Fourth, additional precursor purification using ion mobility separation has the potential to reduce isobaric interference since ion mobility MS separates ions based on charge, size, and shape [72] , [73] , [74] . Using a TMT-based interference standard [75] , high-field asymmetric waveform ion mobility MS (FAIMS) improves the quantitation accuracy of multiplexed quantitative analyses using both high-resolution MS2 and SPS-MS3-based methods [74] .…”
Section: Advantages Disadvantages and Developments Of The Isobaric La...mentioning
confidence: 99%
“…Third, a triethyl ammonium bicarbonate (TEAB) buffer is recommended by the manufacturers of TMT for isobaric labeling. However, the use of 50 mM TEAB in TMT labeling will introduce unidentified and unwanted side reaction substances, such as single charged ions that MS detects with m/z values of 303.26, 317.26, 331.29, and 391.25 [67] , [72] . These substances cannot be removed by RPC desalting.…”
Section: A Better Experimental Workflow For Isobaric Labeling Proteomicsmentioning
confidence: 99%